Highway winter maintenance a practical guide. (ICE design and practice guide., 2000)
This concise new guide reviews current operational arrangements, indicates best practices and suggests the way ahead. To reflect the complexities of the subject the guide covers: operational requirements for winter maintenance; weather forcasting; support technology; research and development; specialist plant and transport; and the role of privatisation.